Complex Interplay between the P-Glycoprotein Multidrug Efflux Pump and the Membrane: Its Role in Modulating Protein Function - Sharom, Frances J. (Frontiers in Oncology, 2014)
Multidrug resistance in cancer is linked to expression of the P-glycoprotein multidrug transporter (Pgp, ABCB1), which exports many structurally diverse compounds from cells. Substrates first partition into the bilayer and then interact with a large flexible binding pocket within the transporter’s transmembrane regions. Pgp has been described as a hydrophobic vacuum cleaner or an outwardly-directed drug/lipid flippase. Recent X-ray crystal structures have shed some light on the nature of the drug-binding pocket and suggested routes by which substrates can enter it from the membrane. Detergents have profound effects on Pgp function, and several appear to be substrates. Biochemical and biophysical studies in vitro, some using purified reconstituted protein, have explored the effects of the membrane environment. They have demonstrated that Pgp is involved in a complex relationship with its lipid environment, which modulates the behaviour of its substrates, as well as various functions of the protein, including ATP hydrolysis, drug binding and drug transport. Membrane lipid composition and fluidity, phospholipid headgroup and acyl chain length all influence Pgp function. Recent studies focusing on thermodynamics and kinetics have revealed some important principles governing Pgp-lipid and substrate-lipid interactions, and how these affect drug binding and transport. In some cells, Pgp is associated with cholesterol-rich microdomains which may modulate its functions. The relationship between Pgp and cholesterol remains an open question; however it clearly affects several aspects of its function in addition to substrate-membrane partitioning. The action of Pgp modulators appears to depend on their membrane permeability, and membrane fluidizers and surfactants reverse drug resistance, likely via an indirect mechanism. A detailed understanding of how the membrane affects Pgp substrates and Pgp’s catalytic cycle may lead to new strategies to combat clinical drug resistance.